Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Sequence $(x_n)$ is difined $x_1=\frac {1}{100}, x_n=-{x_{n-1}}^2+2x_{n-1}, n\ge2$

Prove that $$\sum_{n=1}^\infty [(x_{n+1}-x_n)^2+(x_{n+1}-x_n)(x_{n+2}-x_{n+1})]\lt \frac {1}{3} $$

I found relation $(1-x_n)=(1-x_{n-1})^2$

I don't know what to do next.

There is a real number which is less than $\frac {1}{3}$?

I need your help.

share|cite|improve this question
up vote 1 down vote accepted

A direct proof (note that I've shifted indices from starting at 1 to 0):

First, notice that $x_n\to1$ is the only possible limit. ($x=-x^2+2x \implies (x-1)^2=0$)

[edit] The obvious mistake in my algebra was pointed out -- $x^2=x$ so $x=0$ or $1$. Recentering about $x=0$ doesn't change the recurrence, but recentering about $x=1$, as you can see below, yields a relation that can be solved by inspection.[/edit]

When in doubt, recenter your system about the fixed point; define $a_n=1-x_n$. Then, $$ a_{n+1} = 1-x_{n+1} = 1-[-x_n^2+2x_n] = 1+x_n^2-2x_n=(1-x_n)^2=a_n^2. $$

This allows us to solve the system exactly; $a_n = a_0^{2^n}$, or $1-x_n=(1-x_0)^{2^n}$.

It should now be a matter of algebra to evaluate the sum.

share|cite|improve this answer
No. $x = -x^2+2x \implies x^2-x = 0 \implies x(x-1)=0 \implies x=1$ or $x = 0$. – marty cohen May 13 '14 at 0:27
Can you show me a algebra to evaluate the sum? – user148928 May 13 '14 at 0:32
@marty, oops. :-) But the results are still good. $x=0$ obviously just yields the same recurrence, while $x=1$ will yield the solvable relation. – Jason May 14 '14 at 3:53
@user148928, just substitute the closed form solution to $x_n$. I suspect you'll get something like $(1-x_0)^{2^n+stuff}$. The trick then will be to bound $(1-x_0)^{2^n} < (1-x_0)^n$, then apply geometric series summation formula. – Jason May 14 '14 at 3:57

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.